Theoretical Barriers to the Understanding of Evangelical Christianity - Warner, R. Stephen (Sociological analysis, 1979)
Based on the premise that evangelicalism is an important contemporary phenomenon that has been slighted by sociologists, this paper analyzes three cognitive biases that prevent its understanding. The three biases, or “theoretical barriers,” are the identification of evangelicalism with social class, political, and historical correlates. The paper argues against the assumption that evangelicalism is in essence the religion of the disinherited, the conservative, or the atavistic, especially if we are to understand the resurgence of evangelicalism in mainline and middle-class ch urches.